SISTEM INFORMASI BERCOCOK TANAM HIDROPONIK KELOMPOK TANI FOKUS USAHA BERBASIS WEB - Nurjani, Yeni (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2018)
The information system is a system that provides information for management in making decisions and also to run the companys operations, where the system is a combination of people, information technology and procedures that are organized. Usually a company or business entity provides some sort of useful information for management. At CV. Lintas Nusantara service bureau in data processing activities that are running today still perform administrative data processing conventionally, and also reports given to the pimpiman sometimes still many mistakes. In conducting the research, the authors used several research methodologies, including field research, literature, and laboratories. Furthermore, the information system that has been built is expected to be more helpful CV. Lintas Nusantara Jambi in processing the data better yet to get a more efficient report and also can save time and cost incurred for each month. This information system is built with the support of the Codeigniter PHP Framework, the Bootstrap CSS Framework, as well as the javascript programming language.